Identifikasi Performa Penggunaan Lori Berdasarkan Kegiatan Preventive Maintenance pada Pabrik Kelapa Sawit - Azhar Basyir Rantawi (JURNAL CITRA WIDYA EDUKASI, 2019)
The machines/equipments performance in the production process will contribute to the yield/target of production, so a good maintenance strategy is needed. Buggy is a most important equipment in the palm oil mill, which is a material handling facility. The problem that often arises in this equipment is trouble to the wheels, so it is necessary to identify the causes of trouble, especially in buggy bushing and find out the effect of preventive maintenance on the performance of the bushing, so that the performance of the equipment can be maintained. This research was conducted at the palm oil mill of PT Mitra Mendawai Sejati, Citra Borneo Grup (CBI). Data collection is done by using observation, interview and literature study. The result showed that there were three factors that caused trouble to the buggy wheel, ie the worn wheel shaft, the cleanliness of the area around the buggy and controlling. The time range in actual maintenance scheduling in the field need to be reviewed, so that performance in the use of the buggy can be more optimal.